Phenomenon of Convergence in the Analysis of Economic Growth - Dokurno, Zbigniew (Zjawisko konwergencji w analizie wzrostu gospodarczego, 2010)
The analysis of issues of economic growth leads to the question about the abilities of an economy to adapt its development to the level of development of other economies. Formulated answers to the problem are provided by the analysis of the phenomenon of economic convergence. This approach examines both the causes and determinants of differences in the growth. This leads to the formulation of various measures of the same phenomenon, which takes the form of certain types of convergence. The article presents the essence and the conditions of economic convergence phenomenon and makes a synthesis of its measurement. The conducted considerations lead to the conclusion that within a given economy there should be found such a growth path which would be appropriate for it and which may coincide with the growth paths of economies having similar conditions.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 136, s. 11-20
Keywords: convergence; σ-convergence; absolute convergence; β-convergence; γ-convergence; convergence clubs; economic growth; stochastic convergence; technological convergence